2020
DOI: 10.1108/jedt-04-2020-0146
|View full text |Cite
|
Sign up to set email alerts
|

Critical success factors for adopting building information modelling (BIM) and lean construction practices on construction mega-projects: a Delphi survey

Abstract: Purpose The purpose of this paper is to investigate critical success factors (CSFs) that enhance integration between building information modelling (BIM) and lean construction (LC) practices on construction mega-projects. BIM and LC have gained momentum in the past decade. Design/methodology/approach The Delphi survey technique was used to gauge opinions of a panel of 16 experts through a two-round Delphi questionnaire survey. Panel responses were scrutinised using inferential and descriptive statistical tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 46 publications
2
56
0
2
Order By: Relevance
“…Therefore, the usage of CDE that provides data accessibility is recommended to solve collaboration issues [82]. Evans et al [83] stated that cloud technologies and access to project information have facilitator roles in the performance of waste elimination activities. Furthermore, the usage of CDE helps to share design changes with site within minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the usage of CDE that provides data accessibility is recommended to solve collaboration issues [82]. Evans et al [83] stated that cloud technologies and access to project information have facilitator roles in the performance of waste elimination activities. Furthermore, the usage of CDE helps to share design changes with site within minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Farrell (2016) and Hasson et al (2000) suggest that the Delphi technique is practical to reach agreement amongst a group of experts. While the Delphi technique is recommended in similar situations, Evans et al (2020c) adopted a Delphi technique to investigate the CSFs that enhance integration between BIM and LC practices on construction mega-projects. A dataset was composed over two rounds of Delphi surveys to assess, examine and prioritise barriers to integrating BIM and LC gathered from the extant literature (Hsieh and Shannon, 2005; Grisham, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Azhar et al (2012) investigated BIM trends, critical success factors (CSFs) and barriers that hinder the application of BIM. Evans et al (2020c) investigated the CSFs that enhance integration between BIM and LC practices on construction mega-projects and concluded that the five extreme significant BIM CSFs that boost LeanBIM synergy were “collaboration in design, construction works, and engineering management,” “top organisational management support,” “coordination and planning of construction work,” “earlier and precise 3D visualisation of design,” and “boosting implementation of LC and integrating project delivery.” Chan (2014) considered the barriers of implementing BIM in the construction industry in Hong Kong, and Chan et al (2019) investigated benefits and barriers to implementing BIM in construction. Dave et al (2013) investigated LC implementation in construction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Delphi technique has proven to be a popular and reliable technique for decision making (Adler and Ziglio, 1996;Hallowell and Gambatese, 2010). Over the years, its applications in construction engineering management (CEM) research as a methodology for eliciting knowledge, prioritising elements and decision making, where there is limited knowledge about the research area, has increased greatly (Ameyaw et al, 2016;Ogbeifun et al, 2017;Poghosyan et al, 2020;Evans et al, 2021). In this study, while the comprehensive literature review supported by expert verification enabled elicitation of integrated SHE management capability attributes, the Delphi technique combined with VAHP (a -multi-criteria decision making method) enabled the prioritisation of the attributes.…”
Section: Methodsmentioning
confidence: 99%